The moderating role of readiness for change on the effect of transformational leadership and compensation satisfaction on employee performance: Evidence from post-acquisition companies - Intan Ratnawati; Rr. Retno Sugiharti (Diponegoro International Journal of Business, 2023)
This paper aims to analyze how transformational leadership and compensation satisfaction determine employee performance in post-acquisition companies by proposing readiness for change as a mediating variable. Our samples are 400 employees from four post-acquisition companies which underwent acquisition in 2014. The findings of this study show that the direct effect between transformational leadership and employee performance has a higher value than the indirect effect through the variable readiness for change. Likewise, the direct effect between compensation satisfaction and employee performance has a higher value than the indirect effect through readiness to change. The statement before shows that the existence of readiness to change is essential. Still, the dynamic changes require employees to adapt quickly to new circumstances, ready or not.